FN3 Domain Displaying Double Epitopes: A Cost-Effective Strategy for Producing Substitute Antigens - Ruan, Yao; Chao, Shuangying; Hu, Xuejun; Lu, Longzhen; Lin, Yue; Wang, Qian; Zheng, Yang; Li, Junming; Ding, Ning (Frontiers in Molecular Biosciences, 2021)
onstruction of substitute antigens based on alternative scaffold proteins is a promising strategy in bioassay technology. In this study, we proposed a strategy for constructing substitute antigens derived from 10th human fibronectin type III (FN3) using two peptide epitopes of terminal pro-brain natriuretic peptide (NT-proBNP) as an example. The base sequences encoding the two antigenic epitopes of NT-proBNP were recombined into the FG loop region and the C-terminus of FN3, fused by 4GS or polyN linker. The fusion proteins (named FN3-epitopes-4GS and FN3-epitopes-polyN, respectively) were expressed and purified cost-effectively using an Escherichia coli expression system. The immunoreactivity of recombinant substitutes was preliminarily confirmed by western blot analysis using epitope-specific antibodies. The sandwich enzyme-linked immunosorbent assay (ELISA) demonstrated that either FN3-epitopes-polyN or FN3-epitopes-4GS was highly sensitive, FN3-epitopes-polyN exhibited better kinetics to specific antibodies than FN3-epitopes-4GS, showing a linear dose-response relationship in the concentration range of 0.06-12.85 ng/mL, which suggest that the polyN linker was more suitable for constructing the FN3-based substitute antigens compared to the 4GS linker. Furthermore, the serum stability test and differential scanning calorimetry (DSC) analysis showed that the recombinant FN3-epitopes-polyN maintained the original stability of FN3. Therefore, it was confirmed that FN3 could be engineered to construct a stable biomacromolecular substitute for displaying double epitopes of antigen proteins, such as NT-proBNP. In summary, a cost-effective strategy to produce NT-proBNP substitute antigens with good immunoreactivity and physicochemical stability was established in this work, which may provide potential uses for the production of other substitute antigens in the future.